Pengaruh model pembelajaran think pair and share berbantuan ular tangga diagram batang terhadap kemampuan berpikir kritis siswa kelas V - Ambarwati, Sari; Rini, Zulmi Roestika (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2024)
This study aims to determine the effect of the Think Pair and Share Learning Model on Critical Thinking Ability. The type of research used is quantitative research using experimental methods in the form of a non-equivalent control group design. The population in this study were all students of SD Negeri Gondoriyo, then the research sample was class VA dan VB SD Negeri Gondoriyo. The data collection technique used is the t test while data analysis techniques with normality test, homogeneity test, simple linear regression test and independent sample t test. The results showed: There is an effect of using the think pair and share model assisted snake and ladder bar chart on students' critical thinking skills, as evidenced by the level of tcount = 7.684 > ttable = 2.155 and a significance value <0.05, namely 0.000 <0.05 using a simple linear regression test.